TINDAK TUTUR ILOKUSI AKUN TIKTOK @NAJWASHIHAB SERTA IMPLEMENTASINYA SEBAGAI BAHAN AJAR TEKS PERSUASI - Sri Wahyuningsih; Atiqa Sabardila (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2023)
The purpose of this research is to describe the forms and functions of illocutionary speech acts on the TikTok @najwashihab account, and to describe the implementation of illocutionary speech acts as teaching materials for persuasive texts in junior high schools. This study used a qualitative descriptive method, the data were obtained from Najwashihab's TikTok captions which were observed, read, identified, recorded by researchers for analysis so as to obtain the required illocutionary utterances. This data has the intent and function of influencing the speech partner. The results of this study indicate that there are 55 data found by researchers. The data includes types of directive illocutionary speech acts (28 data), assertive (19 data), and expressive (8 data).